Degrading colour with magnets: degradation of methylene blue MnOx-Fe3O4 using the photo-fenton method - Aulia Rizki Ramadhanti; Amir Awaluddin; Nurhayati Nurhayati; Sri Hilma Siregar (Acta Chimica Asiana, 2025)
One practical approach to reducing methylene blue (MB) levels is through the Advanced Oxidation Processes (AOPs) method, which utilizes hydroxyl radicals (•OH) to degrade the colored compounds. AOPs have proven to be a highly efficient technology in treating coloured wastewater, with the ability to produce strong oxidants that break down molecules that are difficult to decompose naturally. One of the widely used AOP technologies is the Fenton heterogeneous catalyst, which is known for its affordable price, ease of reuse, and the fact that it does not produce solid sludge. In this study, MnOx-Fe3O4 composites were synthesized using the hydrothermal method with variations in the addition of Fe3O4 in ratios of 1:5 and 1:10. Several variables tested in the MB degradation process included the volume of H₂O₂ used (5, 10, and 15 mL), composite contact time, and the effect of pH on degradation efficiency. The results showed that the addition of 5 mL of H₂O₂ to the MnOx-Fe3O4 composite significantly increased the degradation efficiency of methylene blue up to 92.54% within 120 minutes, with an optimal pH of 9. The addition of H₂O₂ was shown to accelerate the degradation process, which shows great potential in wastewater treatment applications. In addition, the magnetic properties of the MnOx-Fe3O4 composite allow easy separation of the catalyst after the treatment process, thus accelerating and facilitating the recovery and reuse of the catalyst. This degradation process involves the formation of hydroxyl radicals (•OH), which are highly reactive and can efficiently break down MB molecules. Thus, this study demonstrates that the MnOx-Fe3O4 composite has the potential to be a highly efficient and environmentally friendly catalyst for treating coloured wastewater. This catalyst is also expected to be reusable in several cycles, making it a sustainable and effective choice in industrial wastewater treatment.